Momentum-based distributed resource scheduling optimization subject to sector-bound nonlinearity and latency - Doostmohammadian, Mohammadreza; Gabidullina, Zulfiya R.; Rabiee, Hamid R. (Systems & control letters, 2025)
This paper proposes an accelerated consensus-based distributed iterative algorithm for resource allocation and scheduling. The proposed gradient-tracking algorithm introduces an auxiliary variable to add momentum towards the optimal state. We prove that this solution is all-time feasible, implying that the coupling constraint always holds along the algorithm iterative procedure; therefore, the algorithm can be terminated at any time. This is in contrast to the ADMM-based solutions that meet constraint feasibility asymptotically. Further, we show that the proposed algorithm can handle possible link nonlinearity due to logarithmically-quantized data transmission (or any sign-preserving odd sector-bound nonlinear mapping). We prove convergence over uniformly-connected dynamic networks (i.e., a hybrid setup) that may occur in mobile and time-varying multi-agent networks. Further, the latency issue over the network is addressed by proposing delay-tolerant solutions. To our best knowledge, accelerated momentum-based convergence, nonlinear linking, all-time feasibility, uniform network connectivity, and handling (possible) time delays are not altogether addressed in the literature. These contributions make our solution practical in many real-world applications. •Introducing accelerated momentum-based algorithm for distributed resource allocation.•Proving all-time feasibility to ensure coupling constraint holds at every iteration•Managing link nonlinearity arising from sign-preserving odd sector-bound mappings.•Proof of convergence over uniformly-connected dynamic networks.•Addressing latency and time-delay issues in network communication.